2021
DOI: 10.1002/ccd.29976
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intravascular ultrasound versus optical coherence tomography guided percutaneous coronary angiography: A meta regression‐based analysis

Abstract: Background: Studies comparing clinical outcomes with intravascular ultrasound (IVUS) versus optical coherence tomography (OCT) guidance for percutaneous coronary intervention (PCI) in patients presenting with coronary artery disease, including stable angina or acute coronary syndrome, are limited. Methods:We performed a detailed search of electronic databases (PubMed, Embase, and Cochrane) for randomized controlled trials and observational studies that compared cardiovascular outcomes of IVUS versus OCT. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Kuku et al pooled data from three RCTs and three observational studies and reported no difference in MACE, cardiac death, MI, TLR, or stent thrombosis between IVUS and OCT 47 . In a more recent meta‐analysis, Sattar et al combined data from four RCTs and three observational studies and found no significant differences between OCT and IVUS across outcomes 40 . Recent trials like the Optical Coherence Tomography Versus Intravascular Ultrasound and Angiography to Guide Percutaneous Coronary Interventions (iSIGHT) trial, the Optical Coherence Tomography Compared with Intravascular Ultrasound and with Angiography to Guide Coronary Stent Implantation (ILUMIEN‐III) trial, and the Optical Frequency Domain Imaging versus Intravascular Ultrasound in Percutaneous Coronary Intervention (OPINION) trial also showed the noninferiority of OCT to IVUS 1,6–9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kuku et al pooled data from three RCTs and three observational studies and reported no difference in MACE, cardiac death, MI, TLR, or stent thrombosis between IVUS and OCT 47 . In a more recent meta‐analysis, Sattar et al combined data from four RCTs and three observational studies and found no significant differences between OCT and IVUS across outcomes 40 . Recent trials like the Optical Coherence Tomography Versus Intravascular Ultrasound and Angiography to Guide Percutaneous Coronary Interventions (iSIGHT) trial, the Optical Coherence Tomography Compared with Intravascular Ultrasound and with Angiography to Guide Coronary Stent Implantation (ILUMIEN‐III) trial, and the Optical Frequency Domain Imaging versus Intravascular Ultrasound in Percutaneous Coronary Intervention (OPINION) trial also showed the noninferiority of OCT to IVUS 1,6–9 .…”
Section: Discussionmentioning
confidence: 99%
“…While many previous meta‐analyses have shown that IVUS‐guided PCI improves outcomes when compared with CA alone, 36–39 our study is unique in that our findings are solely based on RCTs, which are less influenced by unmeasured confounders and selection bias associated with observational studies. Sattar et al and Siddqi et al recently published meta‐analyses on similar topics, but they only included 7 and 13 studies, respectively, about half of which consisted of observational studies 40,41 . In contrast, we incorporated 28 RCTs and produced more robust results by generating network meta‐analyses models under both frequentist and Bayesian frameworks, unlike conventional pairwise meta‐analyses which solely use direct evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An observational study showed a significant difference in mortality between patients who underwent OCT-guided PCI compared with patients who underwent angiography-guided PCI (7.7% vs. 15.7%; p < 0.0001), confirmed also using multivariate Cox analysis (HR 0.48; 95% CI: 0.26 to 0.81; p = 0.001) and propensity matching analysis (HR 0.39; 95% CI: 0.21 to 0.77; p = 0.0008; OCT vs. angiography-alone cohort) [ 104 ]. A recent meta-analysis, encompassing seven studies for a total of 5917 patients, however, failed to demonstrate the superiority of OCT-guided PCI vs. IVUS-guided PCI for hard endpoint MACEs (RR 0.78; 95% CI, 0.57–1.09; p = 0.14) [ 105 ]. Stone and colleagues, finally, showed in the CANARY Trial that near-infrared spectroscopy can identify lipid-rich intracoronary plaques more prone to rupture after stent implantation, generally due to distal embolization [ 82 ].…”
Section: Therapeutic Implication Of Intracoronary Imagingmentioning
confidence: 99%